INVESTIGATION OF DENTURE REMOVAL PROCESS BY MEANS OF DESTRUCTION OF FIXING CEMENT BY ULTRASOUND ACTION - M. G. Kiselev; A. P. Vertinskaya (Наука и техника)
The paper contains results of experimental investigations in respect of denture removal processes using as models so natural teeth as well and this removal process presupposes destruction of fixing cement by ultrasound action. It has been established that the best conditions for separation of a denture from a tooth body are ensured while ultrasound is acting on non-removable denture structure in liquid phase (water). At the expense of sound-capillary effect water fills in porous structure of fixing cement at high speed and a cavitation that appears in it leads to intensive cement destruction (dispersion).